(untitled) (London Journal of Engineering Research, 2025)
Recycled concrete aggregate (RAC) can be used in structural concrete to lessen the environmental impact of waste concrete and the use of natural resources. The current study summarized the mechanical performances of concrete and assessed the synergistic impacts of recycled aggregate, likely at 100% content, with silica fume (SF) partially substituting cement. The study’s primary variables included the dosage of silica fume used as a partial replacement of ordinary Portland cement (OPC) at five different percentages: 0%, 4%, 8%, 12%, and 16% by weight.Five distinct mixtures, designated RACSF-0, RACSF-4, RACSF-8, RACSF-12, and RACSF-16, were made using differing concentrations of silica fume for M30 concrete.The workability of concrete mixes was examined using the slump test. After increasing the proportion of SF, a declining trend was observed in the test results. The mechanical characteristics of RACSF were examined at 7 and 28 days using compressive and splitting tensile tests. The results demonstrated that adding SF enhanced RACSF’s performance at both early and later curing ages, with the highest results occurring at 12% SF addition. As a result, it is advised to partially substitute 12% SF for cement in RAC.